KAJIAN CEKAMAN KEKERINGAN DAN DOSIS PUPUK NITROGEN TERHADAP HASIL PADI GOGO (Oryza sativa L) - Rupa Matheus (Partner, 2010)
The Study of the Droght Stress and The Nitrogen Fertilizer Doses For the Plant Gogo Produce. The research had taken place in glasses house BPTP Naibonat Kupang from Junni to October 2008. The aims of the research is  to know the influences of the value of the drought sress and the nitrogen of Fertilizer doses for the  product of Rice plant Gogo. The research was done by using Randomized Complete Design factorial research which consist of two factors which is used without barren, the droght stess  21 -25 HST, 76 -80 HST and 111 – 115 HST. The secont factor is Nitrogen fertilizer doses which used and without nitrogen fertilizer, 45 kg N/ha, 90 kg N/ha and 135 kg N/ha, with 3 replication. The variabel which observed is the number of plant seed, the panicle number the qualiy of one thousand seeds, the qualiity of the seeds, and harvest index per plantation. The result of the research souws that the effect of drounght and doses nitrogen fertilazer of Riceland field for the fariabel which observed is seed number, the seed quality and the quality of the seed per plantation. The treatmen of the second droht stress (C2) with nitrogen fertilizer doses 90 kg/ha (N2) gives the average seed quality per plantation, whichis higher  than the onther tretment.Keywords: Droght Stress, The Nitrogen Fertilizer Doses and Plant Gogo Produce